222k views
1 vote
A) 18c^2 – 2(3c – 1)^2

В) (2a +3)(a −3) – 2a(4 – 6a)
С) (2x + 3)(3 —2x) - (2x – 5)^2 –10x​

User Jessica
by
4.9k points

1 Answer

4 votes

$$$$$$$$$$$$$$$$$$$$$$$$$$$$$$

====================================

Sorry,

For a), 18c^2 - 18c^2 = 0

Not = 36c^2

A) 18c^2 – 2(3c – 1)^2 В) (2a +3)(a −3) – 2a(4 – 6a) С) (2x + 3)(3 —2x) - (2x – 5)^2 –10x-example-1
A) 18c^2 – 2(3c – 1)^2 В) (2a +3)(a −3) – 2a(4 – 6a) С) (2x + 3)(3 —2x) - (2x – 5)^2 –10x-example-2
User Slazer
by
5.8k points